Providing better culture in elderly care - Chee, Kwan Foong*; Leow, Serena Wai Yee *; Leow, Kenneth (Sun Media Corporation Sdn Bhd, 2023)
This letter is written in light of the recent distressing increase in the number of elderly individuals being discovered deceased at their homes alone.